2007
DOI: 10.1242/jeb.002873
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of gill Na+,K+-ATPaseα- and β-subunits, Na+,K+,2Cl-cotransporter and CFTR anion channel in juvenile anadromous and landlocked Atlantic salmonSalmo salar

Abstract: SUMMARY This study examines changes in gill Na+,K+-ATPase(NKA) α- and β-subunit isoforms,Na+,K+,2Cl- cotransporter (NKCC) and cystic fibrosis transmembrane conductance regulator (CFTR I and II) in anadromous and landlocked strains of Atlantic salmon during parr-smolt transformation, and after seawater (SW) transfer in May/June. Gill NKA activity increased from February through April, May and June among both strains in freshwater (FW),with peak enzyme activity in the landlocked salmon being 50% b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
177
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 225 publications
(212 citation statements)
references
References 57 publications
35
177
0
Order By: Relevance
“…In contrast, the abundance of gill NKAα1a decreased within 2days of seawater exposure and is only a fraction of its initial levels after 14days in seawater. This is consistent with previous research on the influence of salinity on protein abundance ) and gene transcription (Nilsen et al, 2007). This increase probably results in a greater overall capacity for salt secretion in the gill, representing the steady state needed for all activities in seawater.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, the abundance of gill NKAα1a decreased within 2days of seawater exposure and is only a fraction of its initial levels after 14days in seawater. This is consistent with previous research on the influence of salinity on protein abundance ) and gene transcription (Nilsen et al, 2007). This increase probably results in a greater overall capacity for salt secretion in the gill, representing the steady state needed for all activities in seawater.…”
Section: Discussionsupporting
confidence: 92%
“…While a previous study has shown that the abundance of the NKAα1a and NKAα1b isoforms in the gills of Atlantic salmon parr is tightly correlated with environmental salinity, with the NKAα1a being the predominant isoform in freshwater and NKAα1b more abundant after seawater acclimation (McCormick et al, 2009b), the present study is the first to profile the abundance of gill NKAα1a and NKAα1b isoforms during smolt development. Increased gill NKAα1b is consistent with molecular studies demonstrating that transcription of this isoform increases during smolt development of Atlantic salmon (Nilsen et al, 2007). These studies also found that gill NKAα1a mRNA decreases steadily from February to June, whereas in the present study NKAα1a protein levels are relatively stable from February to May with only a minor decrease in the late spring.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations